El sistema de gestión documental y su incidencia en la calidad de atención al usuario - Mora Viejo, Ginger Leonela (2019)
In this case study, information has been gathered on the subject: The Document Management System and its Impact on the Quality of User Care, which used the interview technique with the structured survey tool. This topic is focused on the existing document management systems that achieve the use of administrative personnel, their advantages, these oriented to the objective and myths about them. It also details the quality of customer service and the factors that generate the quality of warmth in customer service. The techniques that were used in this investigation were the survey of users and officials, using the structured survey tool to identify the level of quality of customer service and the document management system that is being used in said secretariat, and thus it will be possible to observe if the authorities need to use a new document management system or not. It is concluded administratively that the document management system used by the institution's officials can process positively in the quality of customer service of EMSABA of the Municipality of Babahoyo